Characteristics of Thrombin-Degranulated Human Platelets: Development of a Method that Does not Use Proteolytic Enzymes for Deaggregation - Kinlough-Rathbone, Raelene L; Packham, Marian A; Guccione, Maria A; Richardson, Mary; Harfenist, Elizabeth J; Mustard, J Fraser (Thrombosis and Haemostasis, 1991)
A method has been developed for preparing suspensions of washed human platelets that have lost as much as 90% of their dense granule and alpha granule contents as a result of stimulation by thrombin (0.9 U/ml for 3 min at 37° C), and recovering the platelets without using a proteolytic erwyme. Glycyl-Lprolyl-Larginyl-L-proline (GPRP) was used to prevent polymerization of released fibrinogen and arginyl-glycyl-aspartyl-serine (RGDS) to block the interaction of released fibrinogen, vWf or fibronectin with the glycoprotein IIb/IIIa complex. The thrombin used to degranulate the platelets was neutralized with D-phenylalanyl-Lprolyl-L-arginine chlororhethyl ketone (FPRCH2CI) and prostaglandin E1 was added to return the platelets towards a disc shape. The degranulated platelets aggregated in response to ADR platelet activating factor, arachidonate and the thromboxane 42 mimetic, U46619 in the presence of added fibrinogen; the platelets changed shape but did not aggregate in response to collagen. Thrombin and the calcium ionophore, A23L87, caused aggregation without added fibrinogen. Synergism between pairs of aggregating agents at low concentrations was observed. Little TXB2 was formed when the platelets were reaggregated by thrombin. RGDS and F(ab’)2 fragments of an antibody to fibrinogen inhibited reaggregation induced by thrombin and A23187 indicating that small amounts of fibrinogen at the platelet surface may support aggregation by strong agonists. Adherence of thrombin-degranulated platelets to a collagen-coated surface was less than for controls, but spreading was more extensive. Electron-microscopic immunogold cytochemistry with anti-human fibrinogen IgG showed numerous gold particles in platelet vacuoles. Thrombin-degranulated platelets can be used to study pathways involved in platelet aggregation without the complicating effects of released granule contents including ADR and to study indirectly the factors released from platelets that contribute to the stability of platelet aggregates.